Generic Challenges: English Epithalamic Tradition and Its Deconstruction (The Case of John Donne) - Krūminienė, Jadvyga (Respectus Philologicus, 2017)
The paper is an attempt at the analysis of generic flexibility as reflected in the minor literary genre of epithalamium, or wedding song. The problem is approached from the reader response and mythopoetic perspective by focusing on John Donne’s Metaphysical instrumentarium employed in the experimental testing of the conventional boundaries. Although, on the one hand, Edmund Spenser’s Epithalamion very successfully follows the Sapphic-Catullan conventions and is regarded as the best creative achievement in English literature, J. Donne’s three epithalamions, in their turn, demonstrate the Baroque virtuosity of transformation. The poet daringly experiments with the responses of both the epithalamic and Metaphysically oriented audience inviting the readers into a challenging rhetorical game. Although he borrows the motifs from classical and Christian nuptial tradition, due to his poetic style marked by the structural and verbal ingenuity, the epithalamic relationships get reordered. The perspective of generic deconstruction with regard to Metaphysical conceited imagery invoked to dramatise the matrimonial marriage as seen in J. Donne’s epithalamions is discussed for the first time in Lithuanian literary criticism.